FORMULAIC EXPRESSIONS USED IN CONVERSATIONAL TEXTS OF THE TENTH GRADE’S ENGLISH TEXTBOOKS - Mustapa, Yaholil; Agustien, Helena I. R. (English Education Journal, 2017)
Formulaic expressions make students become fluent and native-like in English speaking so that formulaic expressions must be introduced a lot to the students in conversational texts of English textbooks. The current study aims at investigating the forms, frequency of occurrence, accuracy, and appropriateness of formulaic expressions in conversational texts of the tenth grader’s English textbooks. This study is a discourse analysis, particularly a text analysis. The objects of the study are fourteen conversational texts taken from the tenth grade’s English textbooks. The results of the study show that there are four forms of formulaic expressions identified in the conversational texts. Moreover, the most frequent form of formulaic expressions in the conversational texts is inserts. It is followed by lexical bundles, idiomatic phrases, and free combinations of verb + particle. Besides, idiomatic phrases and free combinations of verb + particle occur accurately, while lexical bundles and inserts occur both accurately and inaccurately in the conversational texts. In addition, the formulaic expressions appear appropriately and inappropriately in the conversational texts. Based on these findings, there are many conversational texts that do not sound natural; consequently, there must be some revisions.